Development of the Patient's Experience and Attitude Colposcopy Eindhoven Questionnaire (PEACE-q) - Victor J. M. Pop; Tirza Wouters; Ruud L. M. Bekkers; Viola R. M. Spek; Jurgen M. J. Piek (BMC, 2019)
Abstract Background No validated instruments for the evaluation of patient satisfaction in colposcopy do exist. Therefore, this study reports on the development of a Patient's Experience and Attitude to Colposcopy questionnaire. Methods Patients who recently received colposcopy participated in a focus group. A panel of experts evaluated the transcriptions and agreed on a 15-item draft questionnaire. The draft questionnaire was completed by 68 women who subsequently came for a colposcopy. For construct validation, Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were performed as well as reliability analysis. Concurrent validity was assessed with the 4-item Patient Health questionnaire (PHQ-4). Results Construct validation resulted in an 8-item patient perception scale with good psychometric properties (Cronbach's alpha: 0.76) and excellent model fit. Two subscales could be discriminated: patient procedure perception scale (alpha: 0.89) and caregiver attitude perception scale (alpha: 0.71). Both subscales intercorrelated moderately (r = 0.28, p = 0.045). The subscale patient perception correlated significantly with the PHQ-4 scale and its anxiety subscale, not with the depression subscale. Conclusions We developed a Patient's Experience and Attitude to Colposcopy questionnaire with adequate psychometric properties. Future application in out-patient clinics should further evaluate its clinical relevance.